Effects of simulated winter short photoperiods on the microbiome and intestinal metabolism in Huanghe carp (Cyprinus carpio haematopterus) - Wang, Wenqian; Su, Shengyan; Dong, Ping; Feng, Wenrong; Li, Jianlin; Zhang, Chengfeng; Tang, Yongkai (Frontiers in Endocrinology, 2024)
As one of the most important environmental signals, photoperiod plays a crucial role in regulating the growth, metabolism, and survival of organisms. The photoperiod shifts with the transition of the seasons. The difference in photoperiod between summer and winter is the greatest under natural conditions. However, the effect of photoperiod on Huanghe carp (Cyprinus carpio haematopterus) was paid little attention. In this experiment, we conducted an 8-week culture experiment with summer photoperiod (14 h light:10 h dark, n = 60) as the control group and winter photoperiod (10 h light:14 h dark, n = 60) based on the natural laws. We investigated the impact of artificial manipulation of seasonal photoperiod on Huanghe carp by integrating growth performance, intestinal flora, and intestinal metabolome. Winter photoperiod provokes significant weight increases in Huanghe carp. The altered photoperiod contributed to a significant increase in triglyceride and low-density lipoprotein cholesterol levels and the gene expressions of lipid metabolism in the intestine of Huanghe carp. 16s rDNA sequencing revealed that winter photoperiod diminished intestinal flora diversity and altered the abundance. Specifically, the relative abundances of Fusobacteria and Acidobacteriota phyla were higher but Proteobacteria, Firmicutes, and Bacteroidetes phyla were reduced. Analogously, photoperiodic changes induced a significant reduction in the Pseudomonas, Vibrio, Ralstonia, Acinetobacter, and Pseudoalteromonas at the genus level. Additionally, metabolomics analysis showed more than 50% of differential metabolites were associated with phospholipids and inflammation. Microbiome and metabolome correlation analyses revealed that intestinal microbe mediated lipid metabolism alteration. In conclusion, the winter photoperiod induced intestinal flora imbalance and lipid metabolism modification, ultimately affecting the growth of Huanghe carp. This study provides new insights into the effects of seasonal photoperiodic alteration on the well-being of fish.